A profissionalização do adolescente aprendiz no limiar do século XXI - Barbosa, Maria Simara Torres (2006)
This study renders problematic the Learning Program, (Law 10097/2000) developed by SENAC in São Luís-Ma in the period from 2002 to 2004, which has as a goal to prepare teenagers to enter the marketplace. The learning policy concerned to this age group in Brazil is retaking in its historical determinations with recent outline as from the 1990s as a consequence of the deep changes of the contemporary capitalism. Therefore, the analysis is out of way of the tendency that points out the precocious vocational training as something natural and common presented as an innovating solution to face questions that refer to social inequality. It deals with the constitution of institutions that historically played an important function in the teenagers learning system. The goal is to question the policies and ideological determination that gave them an important role. The methodology chosen was the search for the object apprehension in its objective and subjective conditions taking into account a quantitative and qualitative. With a descriptive and critical-analytical approach are presented the specific aspects that constitute the program with the purpose of setting up a possible relation between the learning and the program effects to the teenagers in order to compose a portrait of the learners. It is insignificant the teenagers employment, although important part expresses positive changes in view of knowledge and apprehended attitudes even though this knowledge does not set up favorable relations with the marketplace and with the work position. It is noticed contradictorily the functioning of the precocious vocational training in the scope of the minor apprentice s program developed by SENAC.